Pelatihan Menjaga Kesehatan Gigi Dan Mulut Di Era Normal Baru Pada Murid SMP Tri Ratna – Taman Sari - Marie Louisa; Tien Suwartini; James Handojo; Harryanto Wijaya (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
Maintaining dental and oral health is one of the good habits that must be taught as early as possible, especially in junior high school children. This is because junior high school children are more aware and understand the importance of maintaining health than elementary schoolchildren. As we all know, there is currently a Coronavirus Disease (COVID-19) pandemic, staying at home is considered not to be applied forever. A number of countries have begun to relax policies related to the mobility of their citizens, however, the SARS-CoV-2 virus that causes Covid19 continues to threaten. So, a new lifestyle or new normal will be implemented. The target of the training on maintaining oral health this time is the teachers and students of SMP Tri Ratna. Provide education to students and teachers about the importance of maintaining oral health in the new normal era. The counseling was carried out using a webinar (web seminar), held on February 22, 2022, followed by 132 participants from Tri Ratna Middle School. Participants' knowledge was assessed by pre-test and post-test using Google Form. From the results of the pre-test and post-test obtained, it can be seen that there is an increase in the knowledge of the extension participants by 17.22% (the mean pretest value is 42.78+14.23 and the average posttest value is 60.19+16.87) with an increase in the percentage of correct answers from the prepost test ranging from from 2.63%-36.63%